Peningkatan Pertumbuhan Tanaman Utama Dengan Pemupukan N, P dan K Pada Padi Berpotensi Ratun Tinggi - Yulhasmir Yulhasmir; Susanti Diana; Andi Wijaya (Seminar Nasional Lahan Suboptimal, 2018)
Yulhasmir et al, 2019. Growth enhancement main plant under N, P, and K fertilizer to high ratoon rice potential. pp. 242-248.Nitrogen, phosphor  and potassium  distribution could improve vegetative growth of main plant high potential rice ratoon.  The objective this research was to evaluation vegetative growth  of rice ratoon national varieties with nitrogen, phosphor, and potassium fertilizer.  Using plit plot design with three replicate. Varieties (G) main plot (G1: inpari 6, G2: inpari 10 and G3: inpari 29).  Fertilizer (P) sub plot (P1= Urea 250 kg ha-1, TSP 100 kg ha-1 dan KCl 50 kg ha-1. P2=  Urea  300 kg ha-1, TSP 150 kg ha-1 dan KCl 100 kg ha-1. P3= Urea 300 kg ha-1, TSP 200 kg ha-1 dan KCl 150 kg ha-1).  The result show that inpari 29 significant growth as if plant height, growth tillers inisiation, maximum tillers , flowers inisiation, productive tillers. The fertilizer treatment of  Urea  300 kg ha-1, TSP 150 kg ha-1 dan KCl 100 kg ha-1 beter forvegetative growth.